The Significance of Plea Bargaining in India's Criminal Justice System (Journal of Advances and Scholarly Researches in Allied Education, 2025)
A key component of India's criminal justice system is plea bargaining, which is a negotiated end to criminal prosecutions. The notion, historical development, international viewpoints, and functions of plea bargaining within the Indian legal system are all covered in this article. The idea of plea bargaining is discussed in relation to the criminal justice system, emphasizing how it might speed up case settlement and lessen backlogs in the courts. A historical viewpoint explores the long-standing legal customs in India and charts the development of plea bargaining from antiquity to the present. In particular, the functions and processes described in Cr.P.C. Sections 265A–265L are examined, providing an understanding of the workings of the plea bargaining system in India. The section on the global viewpoint highlights differences in protocols, standards, and protections as it contrasts India's approach to plea bargaining with that of other nations.  Overmore, the article puts light on the importance of plea bargaining in criminal justice system of India.